2022
DOI: 10.1186/s12916-022-02453-7
|View full text |Cite
|
Sign up to set email alerts
|

Urinary symptoms and prostate cancer—the misconception that may be preventing earlier presentation and better survival outcomes

Abstract: Background Prostate cancer is an epidemic of the modern age, and despite efforts to improve awareness, it remains the case that mortality has hardly altered over the decades, driven largely by late presentation. There is a strong public perception that male urinary symptoms is one of the key indicators of prostate cancer, and this continues to be part of messaging from national guidelines and media health campaigns. This narrative, however, is not based on evidence and may be seriously hamperin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Studies have not demonstrated a correlation between urinary symptoms and prostate cancer. 18-20 PSA screening during workup and treatment decision-making should be discussed in older men who commonly may experience LUTS secondary to benign hyperplasia; however, there is minimal indication to screen in young men due to the low risk for cancer. Similar to hypogonadism guidelines, professional recommendations for benign prostatic hyperplasia management range from deferring to prostate cancer screening guidelines to screening “when it would direct management,” the latter which leaves loose interpretation increasing risk for overscreening.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have not demonstrated a correlation between urinary symptoms and prostate cancer. 18-20 PSA screening during workup and treatment decision-making should be discussed in older men who commonly may experience LUTS secondary to benign hyperplasia; however, there is minimal indication to screen in young men due to the low risk for cancer. Similar to hypogonadism guidelines, professional recommendations for benign prostatic hyperplasia management range from deferring to prostate cancer screening guidelines to screening “when it would direct management,” the latter which leaves loose interpretation increasing risk for overscreening.…”
Section: Discussionmentioning
confidence: 99%
“…21 With the patient complaint of a rare symptom of prostate cancer, constipation without any urinary complaints he was immediately referred for prostate cancer screening. 18,[22][23][24] The prompt screening for prostate cancer revealed possible metastasis, whereby the case was referred to the Multidisciplinary Team for review and there it was determined that the cancer was localised and the patient was treated with hormonal and radiotherapy. Following which, the patient's PSA dropped below 1 and has remained at this level for 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…This gap in knowledge may be a significant factor in the initial diagnosis in later stage prostate cancer and diagnosis after metastasis. 17,18 Further this misconception may impact a patient's decision to undergo further prostate screening. 19 The national health service in the UK website lists seven symptoms of prostate cancer, all of which are in reference to urinary tract symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced-stage diagnosis may also arise from delays in the pathway to diagnosis. 9 Despite doubt surrounding the link between lower urinary tract symptoms (LUTS) and prostate cancer, 10 , 11 the absence of prostate cancer screening in the UK means that diagnosis most commonly occurs following presentation to primary care with LUTS, erectile dysfunction, or visible haematuria. 11 , 12 However, a multi-methods study of UK males showed that Black males may not fully disclose possible prostate cancer symptoms during initial consultation in primary care; in addition, the study found that GPs may delay investigation of males in this group, especially if patients have comorbidities, such as diabetes, that share similar symptoms.…”
Section: Introductionmentioning
confidence: 99%